IDENTIFIKASI DAGING SEGAR DAN BUSUK MENGGUNAKAN SENSOR WARNA RGB DAN pH METER DIGITAL - Pambudi, Prastyono Eko; Sutanta, Edhy; -, Mujiman (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2014)
The high demand and limited availability meat in the market cause the pricesto be expensive, and increasingly traders that rotten the meat mixinto the fresh meat. To avoidthe risk, people should know the characteristics ofrotten meat and fresh. This research was development of previous research that develops a to olto identification the fresh meat and rotten with RGB color sensor.This research developed a to olto identification fresh meat and rotten using a digital pH meter senso rbased on value of acidic, basic, or neutral. pH meter works based on pH sensor, theg lass electrode. Digital pH meter works by comparing the potential difference at the sensor electrode with Hions at the meat. By using Op-Amp as a voltage amplifier with higher input impedance, then it can be display a signal voltage(mV) that converted to digital format byt he ADC(Analog to Digital Converter) that it can be displayed and read able on the LCD screen.acidic